Effect of the galvanization process on the fatigue life of high strength steel compression springs - (:unkn) unknown (Walter de Gruyter GmbH, 2021)
In this study, a compression spring fatigue problem arising from the galvanization process was investigated. Fatigue, crack initiation and growth of galvanized and non-galvanized springs manufactured from fully pearlitic high strength steel wires were investigated. According to the results, the galvanized compression springs exhibited a low fatigue life due to hydrogen embrittlement. Hydrogen embrittlement induced crack initiations formed under the galvanizing layer and adversely affect fatigue life. It was observed that local embrittlement on the outer surface of the spring wire causes crack initiations and disperses through the pearlitic interlamellar microstructure. Compared to non-galvanized and shot-peened specimens with the same surface roughness, compression springs, galvanized compression springs exhibited a 25 % reaction force loss at 50 000 cycles. © 2021 Walter de Gruyter GmbH, Berlin/Boston, Germany.
Keywords: Compression springs; Fatigue; Galvanization; High strength steels; Hydrogen assisted cracking